ER:YAG LASER:MINIMAL INVASIVE TECHNIQUE FOR VESTIBULOPLASTY IN THE LOWER JAw - Pisevska, Sofijanka Gerasimova; Simjanovska, Ljuba; Markovska, Mirjana; Petreska, Meri Peeva; Chadikovska, Elizabeta (Journal of Morphological Sciences, 2019)
INTRODUCTION: Vestibuloplasty is a surgical procedure wherein oral vestibule is deepened by changing soft tissue attachments to improve functional vestibular sulcus. In edentulous mandibulae patient with inadequate buccal depth, it is necessary to do surgically detaching the soft tissue attachments. When the benefits and risks of alternative treatment modalities are taken into account for the conventional surgical procedure, minimally invasive laser assisted soft-tissue excision and ablation seems to be very attractive technique. AIM: Main aim of this case report was to evaluate the effect of Er:YAG laser assisted operation technique on post-operative outcome of edentulous patient, undergoing partial vestibuloplasty. METHODS AND MATERIALS: In this case we present the use of Er:YAG laser to change the soft tissue attachments in the oral vestibulum of the lower jaw. A 59- year old patient was refered  to the University Department of oral surgery. After intraoral clinical examination were found complete mandibular edentulism with depth vestibule, sufficient bone height in anterior region and presence of mucosal ligaments. Anterior mandibule vestibuloplasty was planned to prepare the patient for prosthetic rehabilitation. The patient was operated using laser assisted technique for vestibuloplasty with Er:YAG laser (Fotona Fidelis III ) to deep the oral vestibulum. RESULTS: Our results show that Er:YAG laser assisted vestibuloplasty was a minimally invasive surgical procedure with no pain and bleeding. CONCLUSION: Advantiges of laser treatment over conventional metods include minimal cellular destruction, tissue swelling and scarring, hemostasis, minimal or no suturing, reduction in surgical time, postoperative pain and discomfort.